Assimetria flutuante de Paraponera clavata (Fabricius, 1775) em fragmentos urbanos e áreas de regeneração - BEATRIZ OLIVEIRA GARBIN (2024)
Fluctuating asymmetry can be defined as the difference between the right and left sides of an individual, typically influenced by external factors. The aim of this study was to assess the level of fluctuating asymmetry difference in populations of Paraponera clavata (Fabricius, 1775) in urban fragments and regenerating areas. The study was conducted in an area with anthropogenic influence, located within the municipality of Campo Grande, Mato Grosso do Sul, and an area with regeneration time exceeding 40 years, situated at Fazenda Santa Fé, in the municipality of Santa Rita do Pardo, Mato Grosso do Sul. Nests were located, and collections were carried out using the active search method. In addition to measuring the lengths of the antennal scape and femur and tibia of all leg pairs for linear morphometrics, geometric morphometrics were also performed on the head structure. A total of 12 nests were obtained, with seven nests in the APP-UFMS and five nests in Fazenda Santa Fé. The area with greater anthropogenic influence showed a significant difference in PCoA, indicating size variation among collected individuals. Conversely, the area undergoing regeneration exhibited lesser size variation in linear morphometric analysis. When geometric morphometric analyses were conducted, it was concluded that there is fluctuating asymmetry, with no significant difference in the shape of P. clavata heads; however, considering size, a difference was noted, which was more pronounced in the anthropogenically influenced area. Furthermore, it can be inferred that size variation is related to the regeneration and anthropization processes of the areas.